Major international sport profiles - Patel, D. R.; Stier, B.; Luckstead, E. F. (Pediatric Clinics of North America, 2002)
Sports are part of the sociocultural fabric of all countries. Although different sports have their origins in different countries, many sports are now played worldwide. International sporting events bring athletes of many cultures together and provide the opportunity not only for athletic competition but also for sociocultural exchange and understanding among people. This article reviews five major sports with international appeal and participation: cricket, martial arts, field hockey, soccer, and tennis. For each sport, the major aspects of physiological and biomechanical demands, injuries, and prevention strategies are reviewed.